Uber: inovação disruptiva e ciclos de intervenção regulatória - Telésforo, Rachel Lopes (2016)
Technologic innovation is inevitable. Regulation, optional. All over the world, economic trends emerge every moment. Regarding the individual transport system of passengers, focus of this work, sharing economy brought paradigmatic disruptions, as occurred with the arrival of Uber device that offers similar services to taxis and promises to reduce ― or even eliminate ― existing market failures for years. Taxi Market is known for taxis upregulation, and until then, little competition and low consumer satisfaction index. Uber´s presence brought greater expectations of quality, but in the opposite direction of the success with users, the regulator follow the following cycle of intervention all over the world: (i) Immediate app’s prohibition; (ii) Uber’s indirect prohibition, according regulation in accordance with the traditional system/ 'a la taxi' (planning permissions and other mechanisms) and (iii) studies to introduction of a specific regulation, that put together technologic benefices and real attendance to public interest. To look more closely to the cycles, this paper analyzed the regulator’s posture in 23 megacities all over the world, according definition of United Nations – UN, that exemplified agent´s conduct in the cities with more than seven million habitants. Faced with said interventions, this paper has concluded that there is a strong regulatory capture in the transport of passenger’s market ― and there was made a theoretical approach of the Public Choice Theory ― since the first and second cycles evidence benefices of small groups of interest in the sector, rather than the mass. Besides that, since technology can reduce problems involving situations of monopolies, asymmetric information and negative externalities, there is no reason to justify the necessity of maintenance of the regulation, already considered excessive in said market. Also, it is worth mentioning that the regulatory actions were directly countered not only by the popular opinion, but mainly by force of judicial decisions all over the world, that by means of preliminary injunctions prevented abrasive reactions of those agents, and that indicates that judiciary sector is not captured. The third cycle of regulatory intervention indicates a way of interconnection between collaborative economies and urban solutions with the objective of the collective benefice. Studies all over the world points the necessity of regulatory alternatives that can conciliate the public interest with the comprehension of the technologic progress. However, to achieve the third cycle of regulation, it is necessary that the regulator abandon the character merely supervisory and assumes a behavior more analytical and proactive, with the objective of finding regulatory alternatives able to bring gains in infrastructure and urbanization.